The Study on Encapsulation of Copper Nanoparticles in Modified Poly‐Styrene Resin Metrix and its Catalytic Evaluation in Microwave‐Assisted Sonogashira Coupling. Issue 23 (22nd June 2020) - Patel, Sunil B.; Vasava, Dilip V.
Abstract: We have synthesized Cu@Fun.XAD‐16 resin and typified the catalyst by using SEM, HR‐TEM, XRD, RAMAN, XPS, EDX and FT‐IR. From the analysis, we have found the size of zero ‐valent copper nanoparticles was between 10–20 nm, from the XPS analysis, it was confirmed that the Cu was present in both zero‐valent and oxide form. After ensuring the encapsulation we have applied the catalyst in the sonogashira coupling reaction between terminal alkynes and acyl chloride. We have achieved an excellent yield of ynones up to 98 % in the sonogashira coupling reaction by using conventional microwave under solvent‐free conditions. In post reaction TEM, XPS and XRD were studied to ensure the stability of the synthesized catalyst. From the post‐analysis, we have found that there was no notable change take place in the catalyst. We have developed an energy‐efficient and rapid sustainable protocol for the access of various substituted ynones. Abstract : We have modified the inert polymer into a functional polymer and encapsulated the copper nanoparticles in the polymer matrix. The synthesized material was typifying by using SEM, HR‐TEM, XRD, RAMAN, EDS, FT‐IR and XPS. Furthermore, the synthesized catalyst was evaluated for the synthesis of ynone under microwave in neat condition. We have tried scale‐up synthesis and achieved excellent yield. Recyclability and reusability also scanned and it was found that catalyst was recyclable up to 8 times.